Human Capital Development, Energy Consumption and Crude Oil Exports in Nigeria: Implications for Sustainable Development - Aderemi, Timothy Ayomitunde; Adebola, Oyegoke Adebusola; Olanipekun, Wahid Damilola; Peter, Olaoye Olusegun; Bamidele, Ayodeji Gbenga; Ezinwa, Azuh Dominic (International Journal of Energy Economics and Policy, 2021)
This study examined the roles of human capital development, energy consumption and crude oil exports in driving sustainable development goal eight (8)-sustainable economic growth in Nigeria. To achieve this, the authors utilized annual data from 1990 to 2018 which were sourced from World Data Atlas, International Energy Agency, WDI and the Central Bank of Nigeria Statistical Bulletin respectively. Autoregressive Distributed Lag technique of estimation was adopted for the data analysis. Consequently, the principal findings of this research work could be presented as follows; electricity power consumption and growth rate of the real GDP has an insignificant positive relationship with each other. The implication of this is that energy consumption in Nigeria has an inadequate capacity to drive a sustainable economic growth in the country. Similarly, oil exports have a significant positive relationship with the growth rate of the real GDP. This means that economic growth sustainability of Nigeria is highly dependent on oil exports. Conversely, government expenditure on education sector has a significant negative relationship with the growth rate of the real GDP. Also, expenditure of government on health sector has a negative but insignificant relationship with the growth rate of the real GDP. This implies that human capital development in Nigeria lack the capacity to ensure a sustainable economic growth. In view of the above, this study makes the following recommendations for the policymakers in Nigeria and by extension developing countries, any time the goal of these policymakers are sustainable economic growth, the development of human capital through adequate funding of educational and health sectors should be embarked upon. In the same vein, the policymakers should provide uninterrupted electricity supply for enhancement of maximum outputs in the country. Keywords: Human Capital, Energy Consumption, Oil Exports, SDGs JEL Classifications: L94, F63, I15, I25 DOI: https://doi.org/10.32479/ijeep.8488